Can bronchial secretion cultures identify the etiologic agent of COVID-19-associated pulmonary aspergillosis in ICU patients? Comparison with a species-specific Aspergillus PCR in serum. (7th December 2022) - Siopi, Maria; Antonopoulou, Stavroula; Mantzana, Paraskevi; Georgiou, Panagiota-Christina; Vourli, Sophia; Protonotariou, Efthymia; Vagiakou, Eleni; Skoura, Lemonia; Pournaras, Spyros; Meletiadis, Joseph
Abstract: Aspergillus spp. isolated from non-BAL cultures of coronavirus disease 2019 (COVID-19)-associated pulmonary aspergillosis (CAPA) patients may reflect colonization rather than infection. Sera ( n  = 181) from 49 adult ICU CAPA patients (24 probable and 25 possible CAPA) with bronchial secretions (BS) culture positive for Aspergillus spp. were collected and tested for Aspergillus DNA detection by species-specific real-time PCR. Overall, 30/49 (61%) patients were PCR positive. BS culture/serum PCR agreement was moderate (21/30; 70%). Based on serum PCR positive patients, all CAPAs were due to A. fumigatus (80%), A. flavus (10%), and A. terreus (10%). No A. niger / A. nidulans or mixed infections were found despite positive BS cultures. Lay Summary: Discordant results were observed between bronchial secretion cultures and species-specific serum PCR (30%) with A. fumigatus being by far the most common etiological agent of CAPA (80%). No A. niger / A. nidulans or mixed infections were found despite positive cultures.